USING LYRICS LINES TO STRENGTHEN READING COMPREHENSION - edy suseno (ELT Worldwide: Journal of English Language Teaching, 2018)
ABSTRACTThe way to persuade students to read texts is sometimes frustrating. They are reluctant to explore a lot of knowledge by reading some books or articles. This kind of condition is not good for the students to increase their perspective of knowledge. Experiencing such a thing, the teachers feel dismayed whenever see the result of their students’ reading test is low. Many teachers try many methods to adapt in order to invite their students to get involved in reading practice. It is very important to find out a proper way to imply a method to enhance the students reading the material accordingly.  Nevertheless, songs are parts of life all around the world people love to listen. Meanwhile, most of the students are fond of singing or listening to the songs. They copy the singers’ utterances by reading lyrics to express their intention to others. Moreover, learning lyrics means to read the extensive reading. So that by posing lyrics often to discuss with makes students be accustomed to comprehending the content of the various texts. Step by step they start loving reading.  Finally, their competence to grab the message of the texts is enhanced.